Quarter - Century Experience in Cryopreservation of Human Oocytes by Vitrification. What Has Been Achieved and What is Next? - Yurchuk, Taisiia; Petrushko, Maryna (Problems of Cryobiology and Cryomedicine, 2023)
Cryopreservation of human oocytes by the vitrification has become a part of the daily practice of assisted reproductive technologies to fight an infertility and to preserve the woman's reproductive potential. This literature review covers the results of the studies performed by various scientific schools during 25 years; historical prerequisites for the development of cryopreservation of human oocytes by vitrification; medical and social indices to apply this method, features and complications arising during vitrification of human oocytes. Special attention has been paid to the issues regarding the genetic safety of the method mentioned in respect of the health of future descendants. The paper presents the insight on unsolved tasks in vitrification of oocytes and that of identified ways to overcome the challenges. Probl Cryobiol Cryomed 2023; 33(3):177–192